Ontogeny of Neuro-Insular Complexes and Islets Innervation in the Human Pancreas - Proshchina, Alexandra E.; Krivova, Yulia S.; Barabanov, Valeriy M.; Saveliev, Sergey V. (Frontiers in Endocrinology, 2014)
The ontogeny of the neuro-insular complexes (NIC) and the islets innervation in human pancreas has not been studied in detail. Our aim was to describe the developmental dynamics and distribution of the nervous system structures in the endocrine part of human pancreas. We used doublestaining with antibodies specific to pan-neural markers (neuron-specific enolase (NSE) and S100 protein) and to hormones of pancreatic endocrine cells. NSE and S100-positive nerves and ganglia were identified in the human fetal pancreas from gestation week (gw) 10 onwards. Later the density of S100 and NSE-positive fibers increased. In adults this network was sparse. The islets innervation started to form from gw 14. NSE-containing endocrine cells were identified from gw 12 onwards. Additionally, S100-positive cells were detected both in the periphery and within some of the islets starting at gw 14. The analysis of islets innervation has shown that the fetal pancreas contained neuro-insular complexes and the number of these complexes was reduced in adults. The highest density of neuro-insular complexes is detected during middle and late fetal periods, when the mosaic islets, typical for adults, form. The close integration between the developing pancreatic islets and the nervous system structures may play an important role not only in the hormone secretion, but also in the islets morphogenesis.